About the influence of a water-based priming system on the interactions between wood and one-component polyurethane adhesive studied by atomic force microscopy and confocal Raman spectroscopy imaging. (January 2018) - Casdorff, Kirstin; Kläusler, Oliver; Gabriel, Joseph; Amen, Carlos; Lehringer, Christian; Burgert, Ingo; Keplinger, Tobias
Abstract: In recent years one-component polyurethane (1C-PUR) adhesives have been increasingly applied in loadbearing timber constructions. However, a low wood fracture percentage at wet stage and a comparatively low performance in delamination tests need to be overcome to fulfill certain technical standards and to achieve an even higher acceptance in the global market of wood adhesives. Via the use of suitable primers, in this case a water-soluble primer (WSP) system, it is possible to significantly improve these parameters. Nevertheless, the exact mode of action of the primer remains so far unclear. In this study, primer treated wood surfaces were characterized in detail by atomic force microscopy (AFM) and the influence of the primer on the penetration of the 1C-PUR adhesive into wood cell walls was further analyzed by confocal Raman spectroscopy imaging. AFM investigations of primer treated surfaces reveal a significant increase in adhesion compared to non-primer treated surfaces and indicate a penetration of the primer into the cell wall. However, Raman spectroscopy shows that the primer application does not lead to a substantial and deep penetration of the 1C-PUR adhesive into wood cell walls. Slight changes in the spectral properties of the primer treated samples at the interface between the bond line and the adjacent cell wall, point towards changed interactions between wood and polyurethane.